2015
DOI: 10.7763/ijssh.2015.v5.502
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Sustaining the Malay Traditional Kuih among Youth

Abstract: Abstract-The purpose of the article is to disclose the challenges in sustaining the Malay traditional kuih with differing levels of acceptance among youth in East Coast Peninsular Malaysia. Malay kuih also known as Malay dessert that referring to a product which uses specific raw ingredients; methods; processes; techniques; materials and utensils; and the recipes have been passed down from one generation to other generations. It is part of Malaysian culture, identity and heritage that should be sustained by al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…With this, the distinct culinary features also said to face dilution through the globalization and modernization. A similar situation reported on the traditional Malay cuisine as more and more studies proven its prevalence like in the studies of [13,18,42,44,45]. It is however, seemingly promising for the Nyonya kuih to thrive as [11] discussed that the culture of Baba Nyonya has been entering the limelight of attention in book publications, theses, and other public awareness events.…”
Section: Malay Kuih and Nyonya Kuih Debaclesupporting
confidence: 55%
See 2 more Smart Citations
“…With this, the distinct culinary features also said to face dilution through the globalization and modernization. A similar situation reported on the traditional Malay cuisine as more and more studies proven its prevalence like in the studies of [13,18,42,44,45]. It is however, seemingly promising for the Nyonya kuih to thrive as [11] discussed that the culture of Baba Nyonya has been entering the limelight of attention in book publications, theses, and other public awareness events.…”
Section: Malay Kuih and Nyonya Kuih Debaclesupporting
confidence: 55%
“…Karipap (curry puffs), apam (steamed sponge cakes), and keria (donut like kuih made from sweet potatoes and glazed in crystalized sugar) are some examples that fall into the typically found variety. These delicacies are treated as intangible heritage by the Malays and have been passed down verbally from generation to generations especially within the womenfolk [18]. Not to mention also that the habit and acceptance of new generations to consume traditional Malay kuih are inevitably have to be embedded in the family itself.…”
Section: Traditional Malay Kuih: An Array Of Traditional Sensesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferences of traditional foods as the leading definition of FH and its relationship to food transferred from one generation to another been supported by the previous researcher stated that traditional food as part of culture, identity, and heritage of countries all around the world. It is also as a means of usage in the community for a period, showing the transmission between generations (Hamzah et al, 2015;Sharif, Zahari, Nor, & Muhammad, 2013). It also linked with celebration and related to a special occasion (Vitterso & Amilien, 2011).…”
Section: Respondent Profilementioning
confidence: 99%
“…With the incoming of globalized trends and changes in lifestyles among youth, traditional family businesses may not be able to thrive as they have been in the last fifty years. In a study on sustaining the Malay traditional food among youth, Hamzah et al (2015) identified six factors that can influence the continuance of cultural heritage: influence of family, cultural values and personal values, the knowledge inherited from earlier generations, motivation to get involved, incorporating parts of the traditions as a way of life, and benefit to one's income and living. These factors are also relevant to other types of local products such as the batik and songket, the production of dried seafood, crafts, and others.…”
Section: Discussionmentioning
confidence: 99%